SOME ASPECTS OF TECHNOLOGICAL PROCESS OF CASTINGS IN COATED CHILL - A. N. Krutilin; R. E. Trubitskij; I. V. Rafalskij; I. V. Lushchik (Литьë и металлургия)
Analysis of technological process of pouring into coated iron chill is presented. It is shown that the process is very sensitive to the change of technological parameters, is rather complex in regulation and control.